THE USE OF SURGICAL ADHESIVE AND SUTURE FIXING MESHES TO THE ABDOMINAL WALL: AN EXPERIMENTAL STUDY IN RATS - UTRABO,Carlos Alberto Lima (2022)
ABSTRACT - BACKGROUND: Proper fixation of the surgical mesh determines the success of a herniorrhaphy. Understanding the inflammatory response and the mechanical properties of the mesh helps to define whether a fixation method is superior. AIM: This study aimed to evaluate the healing of defects in the abdominal wall of rats, comparing the repair of macroporous polypropylene meshes fixed with surgical glue and polypropylene thread. METHODS: In 20 Wistar rats, a defect was produced in the abdominal wall, with the integrity of the parietal peritoneum. For correction, the meshes were fixed with surgical glue (2-octyl cyanoacrylate) (subgroup C1), or polypropylene suture (subgroup C2). The two subgroups of 10 animals were euthanized on the 90th postoperative day, and the fragments of the abdominal wall were submitted to macroscopic, histological, and tensiometric analysis. RESULTS: Macroscopic analysis did not show any abnormalities. Tensiometry on the 90th postoperative day in subgroup C1 showed mean rupture tension of 28.47N and in subgroup C2 32.06N (p=0.773). The inflammatory process score revealed that both groups are in the subacute phase (p=0.380). CONCLUSION: The fixation of a polypropylene macroporous mesh to repair an abdominal wall defect can be performed with surgical glue (2-octyl cyanoacrylate) or polypropylene suture, both methods being equally effective.